Analysis Of The Influence Of The Use Of Digital Tourism On The Interest In Visiting Generation Z At The Bank Indonesia Museum - Winata, Rachel; Berutu, Feronika (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2025)
This study is to examine how the use of digital tourism affects generation Z tourists interest in visiting Museum Bank Indonesia. Digital tourism is seen as a type of technological adaption in the travel industry that might draw in young travelers who grew up in the digital age. A questionnaire was distributed to 100 members of Generation Z who had visited Museum Bank Indonesia as a part of this study’s quantitative survey methodology. To analyze the data in this study using simple linear regression. The analysis’s findings, which include a regression coefficient value of 0,594 and a significance value of 0,000 < 0,05, demonstrate that digital tourism significantly and favorably influences visitor interest. Therefore, the employment of digital technology in museums has been successful in promoting a rise in visitor numbers, particularly in Generation Z.